О методе сравнения для импульсных систем в пространстве R - Ахметов, М.У.; Перестюк, М.О. (Український математичний журнал, 1993)
A method of study of differential equations with an impulse action on a surface, applied in [1] for a bounded part of the phase space, is now being extended to the whole space